PENGUATAN KARAKTER TANGGUNG JAWAB DAN KEMANDIRIAN PADA MAHASISWA PPKN MELALUI PERKULIAHAN KEPRAMUKAAN DALAM UPAYA MEMPERSIAPKAN MUTU LULUSAN SEBAGAI PEMBINA EKSTRAKURIKULER DI SEKOLAH - Arfiah, Sri; Sumardjoko, Bambang (Jurnal Pendidikan Ilmu Sosial, 2017)
The existence of kepramukaan subject (scouting) is one of many ways to acquire vision and mission of PPKn FKIP UMS. The study found three major findings. First of all, the implementation of subject kepramukaan was related to responsibility and independency characteristic reinforcement held in first and second semester and followed by field activity in fourth and sixth semester. Secondly, students assumed that this subject was critical, especially on character building as a teacher candidate and extracurricular tutor at school. Thirdly, the alumni and stakeholders thought that Kepramukaan studies was very supportive in term of responsibility and independency character building and finally improve the graduate quality.